Primary malignant mixed müllerian tumor of the peritoneum a case report with review of the literature - Kurshumliu, Fisnik (BioMed Central, 2011)
Malignant mixed Müllerian tumor is a rare malignancy of the genital tract and extremely uncommon in extragenital sites. This report describes a case of malignant mixed Müllerian tumor arising in the lower peritoneum of a 72-year-old female patient. The patient presented with ascites, lower abdominal mass and pleural effusion. The serum level of CA125 was elevated. At operation a diffuse carcinosis associated with tumor mass measuring 20 × 15 × 10 cm in the vesicouterine and Duglas' pouch were found. The uterus and the adnexa were unremarkable. Histopathology revealed a typical malignant mixed Müllerian tumor, heterologous type. The epithelial component was positive for cytokeratin 7 and vimentin whereas the mesenchymal component was positive for Vimentin, S100 and focally for CK7. The histogenesis of this tumor arising from the peritoneum is still speculative. Based on the previous reports and the immunohistochemical analysis of our case, we believe that this is a monoclonal tumor with carcinoma being the "precursor" element. Nevertheless, further molecular and genetic evidence is needed to support such a conclusion.